The role of the nurse in the formation of health policy - Lemonidou, Chryssoula; Merkouris, Anastasios (My University, 1998)
Although nurses constitute the majority of health professionals and they are in direct contact with healthy or sick individuals in all kind of health facilities, many of the decisions concerning nursing are made by physicians, administrators or other health professionals. The major problems facing nursing in Greece that lead to that situation include: 1) lack of definition of nursing care, 2} shortage of registered nurses, and 3) three different and competitive educational levels.